2016
DOI: 10.4172/2469-9837.1000175
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Spiritual Values among School Children

Abstract: Spiritual values are the integrated values towards the spiritual development of children. The present study is broadly aimed at identifying and assessing spiritual values among school children. The sample of 104 school children was drawn from grade 5th to grade 8th from different schools of Aligarh city. Of these, 46 children were females and 58 were males. Simple random sampling technique was used to select participants to the sample. The objectives of the present study were: (1) to identify spiritual values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Performance anxiety, characterized by fear and distress regarding one’s ability to perform a specific task, can affect any type of task including everyday activities (Osborne et al, 2014; Robichaud & Dugas, 2015). Numerous studies have demonstrated the effectiveness of psychological interventions, such as cognitive-behavioral therapy, mental imagery, relaxation techniques, and other approaches, in reducing athletic anxiety, increasing performance, and enhancing athletes’ competitiveness (Dehghani et al, 2018; Finch & Moscovitch, 2016; Nazam & Husain, 2014). Cheng and Hardy’s (2016) study highlights that performance anxiety is a negative psychological state that arises from performing a task under pressure, which can be caused by external and internal threats, as well as an individual’s ability to cope with them and meet the demands of the task in sports.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Performance anxiety, characterized by fear and distress regarding one’s ability to perform a specific task, can affect any type of task including everyday activities (Osborne et al, 2014; Robichaud & Dugas, 2015). Numerous studies have demonstrated the effectiveness of psychological interventions, such as cognitive-behavioral therapy, mental imagery, relaxation techniques, and other approaches, in reducing athletic anxiety, increasing performance, and enhancing athletes’ competitiveness (Dehghani et al, 2018; Finch & Moscovitch, 2016; Nazam & Husain, 2014). Cheng and Hardy’s (2016) study highlights that performance anxiety is a negative psychological state that arises from performing a task under pressure, which can be caused by external and internal threats, as well as an individual’s ability to cope with them and meet the demands of the task in sports.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Nazam and Husain [135] identified 28 spiritual values in personality formation when analyzing spiritual values among students: courage, charity, creativity, cheerfulness, caring, discipline, equality, faithfulness, goodness, honesty, humility, happiness, helping, hard work, humorous, kindness, mannerism, obedience, punctuality, peace, polite, social, sharing, sacrifice, sincerity, simplicity, truthfulness, and the value of being understanding. Researchers believe that spiritual values are irreplaceable in children's spiritual development.…”
mentioning
confidence: 99%